2011
DOI: 10.2967/jnumed.110.079624
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Clinical PET/CT Operations: Results of an International Survey of Active PET/CT Users

Abstract: This study gathered information about clinical PET/CT operations worldwide to help guide discussions on the use and standardization of clinical PET/CT. Methods: A Web-based survey of PET/CT users was initiated in November 2009 through e-mail advertising using Academy of Molecular Imaging databases. Recipients were asked 58 questions related to demographics (e.g., location, number of PET/CT systems, and staffing), PET/CT operations and use, and variations in 18 F-FDG oncology imaging protocols. Results: The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
99
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 29 publications
2
99
2
4
Order By: Relevance
“…Nevertheless, an international survey performed in 2011 demonstrated that the majority of PET/CT users still employed CT contrast agents in only a small proportion of patients [22]. Likewise, in a survey performed in 2014 among international SPECT/CT users, an overwhelming majority of respondents wanted to employ their SPECT/CT system as a SPECT system with attenuation correction and coarse anatomical localization rather than to implement closer integration of radiology-driven imaging perspectives [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an international survey performed in 2011 demonstrated that the majority of PET/CT users still employed CT contrast agents in only a small proportion of patients [22]. Likewise, in a survey performed in 2014 among international SPECT/CT users, an overwhelming majority of respondents wanted to employ their SPECT/CT system as a SPECT system with attenuation correction and coarse anatomical localization rather than to implement closer integration of radiology-driven imaging perspectives [23].…”
mentioning
confidence: 99%
“…Although only a minority of groups have adapted PET/CT acquisition protocols to optimize information obtained from both the nuclear medicine and the radiology perspective they have documented convincing positive results [20,21]. And while the Bnuclear medicine approach^dominates in Europe and the Bradiology approach^is more common in the US, the paucity of truly combined reporting of hybrid imaging is independent of geographical location [22,23].…”
mentioning
confidence: 99%
“…A recent survey among SPECT/CT users [11] found that the majority of examinations are performed with little attention to the CT element. Likewise, few users of PET/CT utilize the full potential of the CT element through the use of radiology-equivalent protocols [12]. This is in addition to a general variability in adhering to imaging standards [13].…”
mentioning
confidence: 99%
“…Often, use of these new technologies is preferred by the nuclear medicine physicians for visual assessment of the images [16,17]. At the same time use of these new technologies may result in a wider variability (and change) of SUV across different centres [16,19,21]. Moreover, use of the maximum SUV (SUV max ), being the de facto standard in many studies, in combination with these new technologies may even worsen accuracy and precision [19,22].…”
mentioning
confidence: 99%